Java Memory Management A Comprehensive Guide to Garbage Collection and JVM Tuning - Putten, Maaike van; Kennedy, Seán (Packt Publishing, Limited, 2022)
Improve application performance by tuning, monitoring and profiling both the garbage collector and JVM Key Features Understand the different parts of Java memory and the various garbage collectors so you can select your preferred one Explore how memory management can help to effectively improve performance Learn how to spot and avoid memory leaks to enhance application performance Book Description Understanding how Java organizes memory is important for every Java professional, but this particular topic is a common knowledge gap for many software professionals. Having in-depth knowledge of memory functioning and management is incredibly useful in writing and analyzing code, as well as debugging memory problems. In fact, it can be just the knowledge you need to level up your skills and career. In this book, you'll start by working through the basics of Java memory. After that, you'll dive into the different segments individually. You'll explore the stack, the heap, and the Metaspace. Next, you'll be ready to delve into JVM standard garbage collectors. The book will also show you how to tune, monitor and profile JVM memory management. Later chapters will guide you on how to avoid and spot memory leaks. By the end of this book, you'll have understood how Java manages memory and how to customize it for the benefit of your applications. What you will learn Understand the schematics of debugging and how to design the application to perform well Discover how garbage collectors work Distinguish between various garbage collector implementations Identify the metrics required for analyzing application performance Configure and monitor JVM memory management Identify and solve memory leaks Who this book is for This book is for all levels of Java professionals, regardless of whether you're a junior or senior developer, a DevOps engineer, a tester, or the system admin of a Java application. If you currently don't have in-depth knowledge of Java memory, garbage collection, and/or JVM tuning, then this book will help you to take your Java skills to the next level.
Includes index. - Description based upon print version of record
Keywords: Java (Computer program language); Memory management (Computer science); Java (Langage de programmation); Gestion mémoire (Informatique)